The impact of employee compensation restrictions on labor productivity in state-owned enterprises: Evidence from China - Zhu, Bao; Ma, Zhong; Qu, Xiaojie (Frontiers in Psychology, 2022)
Employees are important stakeholders in an organization. This paper aims to examine the effectiveness of limits on employee compensation in state-owned enterprises (SOEs), a policy for employees of state-owned enterprises issued by the China State-owned Assets Supervision and Administration Commission (SASAC) in 2010. Employing a difference-in-differences analysis for a sample of Chinese listed companies from 2007 to 2013, the results show that employee compensation restriction enhances the labor productivity of SOEs. This policy effect is mainly due to the contribution of compensation limits to the external fairness of employee compensation, and the findings remain unchanged after a series of robustness testing procedures. In addition, the employee compensation restriction policy significantly affects labor productivity improvement in monopolistic industries or mature SOEs.